2015
DOI: 10.5455/2320-6012.ijrms20150140
|View full text |Cite
|
Sign up to set email alerts
|

To study the effect of glycemic control and duration of disease on pulmonary function tests and diffusion capacity in type 2 diabetes mellitus

Abstract: Diabetes mellitus is a public health problem in developing and developed world. There is an alarming increase in the incidence and prevalence of diabetes mellitus particularly in Asian Indians. According to WHO India will be world diabetic capital in 2025. 1 Diabetes mellitus is associated with widespread hormonal, metabolic, and microvascular abnormalities, as well as with disturbances of the function of many organ systems. The macroangiopathic and microangiopathic complications affect eyes, kidneys, nerves, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 22 publications
(23 reference statements)
2
7
0
Order By: Relevance
“…These changes increase the thickness of collagen molecules as well as the pulmonary capillary network, thereby narrowing the alveolar-capillary membrane. These results were in line with the findings obtained by Zineldin et al, Fuso et al, and Singh et al [13,19,20]. They reported dimin- ished pulmonary volumes and end tidal carbon dioxide pressure in patients with type 2 diabetes compared with healthy individuals.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These changes increase the thickness of collagen molecules as well as the pulmonary capillary network, thereby narrowing the alveolar-capillary membrane. These results were in line with the findings obtained by Zineldin et al, Fuso et al, and Singh et al [13,19,20]. They reported dimin- ished pulmonary volumes and end tidal carbon dioxide pressure in patients with type 2 diabetes compared with healthy individuals.…”
Section: Discussionsupporting
confidence: 92%
“…Meanwhile, these studies assess volumetric parameters of lung such as Forced Vital Capacity (FVC) and Forced Expiratory Volume in one second (FEV1) using a spirometer [10,11]. Also, this diminished function in the lungs shows an inverse relationship with the blood sugar level and duration of having diabetes [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…They argued that glycated Haemoglobin (HbA1c) level is an indicator of glycemic control for a short period of one to two months and that short duration of hyperglycemia was not adequate to in°uence PFTs. However, Davis et al, 14 Jamatia et al 45 and Singh et al 46 observed a negative correlation between pulmonary function and glycemic levels, indicating that a poor lung function was associated with a poor glycemic control. These authors did not explain the exact pathophysiological mechanism for this association.…”
Section: Discussionmentioning
confidence: 95%
“…45 and Singh et al. 46 observed a negative correlation between pulmonary function and glycemic levels, indicating that a poor lung function was associated with a poor glycemic control. These authors did not explain the exact pathophysiological mechanism for this association.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation